Analysis of Ways to Increase Profit in Industrial Enterprises - Gafurova Aziza Fatikhovna (Peerian Journals Publishing, 2022)
In this article, the factors affecting the increase in the profit of economic entities, the maximum increase in the amount of profit remaining from the company’s income, and the factors affecting the increase in profit, the factors of increasing income are studied. Also, regional analysis of industrial enterprises, state of growth of industrial enterprises profit per capita and opinions of foreign and local scientists from the point of view of industrial enterprises profit were studied, and specific analytical and statistical data were presented.
Keywords: labor productivity; costs; costsprofit sizes